Development Of Domestic Tourism In Uzbekistan: Analysis And Strategic Approaches (Eurasian Research Bulletin, 2026)
Scientific-methodological research is being conducted globally to develop domestic tourism in various countries. These studies address important issues such as identifying trends in the development of domestic tourism and strengthening collaboration between the government, organizations, and tourists